2022
DOI: 10.1111/ijfs.15936
|View full text |Cite
|
Sign up to set email alerts
|

Role of phenolic acid, tannins, stilbenes, lignans and flavonoids in human health – a review

Abstract: Phytonutrients such as phenolics play important roles in health and well-being. The main phenolic compounds include phenolic acid, tannins, stilbenes, lignans and flavonoids. Phenolic compounds in plants distributed in the tissues, cell walls and subcellular compartments have biological activities, including antioxidant, chemopreventive, neuroprotective, cardioprotective and immunomodulatory properties. Citrus fruits, herbs and cereals are a few examples of flavonoid sources with biological functions. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…lemon) as a result of its bioactive compounds is beneficial to human health because it stimulates specific metabolic activities that protect tissues and fluids from damage associated with reactive oxygen species, thus maintaining cell structure and functions and inhibiting lipid peroxidation 79 . Moreover, antioxidant activity is considered to trigger other biological functions such as anti‐inflammation or anti‐cancer activities 80 …”
Section: Discussionmentioning
confidence: 99%
“…lemon) as a result of its bioactive compounds is beneficial to human health because it stimulates specific metabolic activities that protect tissues and fluids from damage associated with reactive oxygen species, thus maintaining cell structure and functions and inhibiting lipid peroxidation 79 . Moreover, antioxidant activity is considered to trigger other biological functions such as anti‐inflammation or anti‐cancer activities 80 …”
Section: Discussionmentioning
confidence: 99%
“…This nexus between food ingredients and optimisation of human health was further illustrated by Oluwole et al (2022) who showed that phytonutrients such as plant phenolics play important roles in health and well-being. Leichtweis et al (2021) explored the potential of using bioresidues from the food industry to enhance nutritional properties of foods.…”
Section: Plant Polyphenolic Compounds and Healthmentioning
confidence: 97%
“…This nexus between food ingredients and optimisation of human health was further illustrated by Oluwole et al . (2022) who showed that phytonutrients such as plant phenolics play important roles in health and well‐being. Leichtweis et al .…”
Section: Plant Polyphenolic Compounds and Healthmentioning
confidence: 99%
“…[1,4] In addition to prevention, interest is also focused on the study of new compounds that can be used for therapeutic purposes and have pharmacological properties. [5] Hydroxylated stilbenes are compounds that seem to have both antioxidant and pharmacological properties, which means that they can be useful not only in prevention but also in therapy. [6] Considering this, but also the fact that these compounds are found in nature in at least 72 plant species, it is not surprising that hydroxylated stilbenes are increasingly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more and more people tend to live healthier by adjusting their diet and consuming many antioxidants that help prevent oxidative damage [1,4] . In addition to prevention, interest is also focused on the study of new compounds that can be used for therapeutic purposes and have pharmacological properties [5] . Hydroxylated stilbenes are compounds that seem to have both antioxidant and pharmacological properties, which means that they can be useful not only in prevention but also in therapy [6] .…”
Section: Introductionmentioning
confidence: 99%